2018
DOI: 10.1784/204764218823931271
|View full text |Cite
|
Sign up to set email alerts
|

A study of white etching crack bearing failure detection using electrostatic sensing in wind turbine gearboxes

Abstract: White etching cracks (WECs) have been found to form in rolling element bearings as early as 6-24 months into operation, especially in large wind turbine gearboxes [1] . [2,3] . [4] . [3] . To investigate the feasibility of WEC detection using the electrostatic (ES) sensing technique, an ES wear site sensor was installed on a bearing test-rig where WECs had been created under the influence of electrical load. The ES responses were compared with those from an acoustic emission (AE) sensor that had been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Electromagnetism-based strategies are less commonly found for CM, except for some applications of electrostatic monitoring of WT gearboxes [240], often resorting to a single [240,241] or multiple [242] oil-line electrostatic sensors. The concept has been tested for WECs in WT gearboxes as well [243].…”
Section: Electromagnetic Testing (Et)mentioning
confidence: 99%
“…Electromagnetism-based strategies are less commonly found for CM, except for some applications of electrostatic monitoring of WT gearboxes [240], often resorting to a single [240,241] or multiple [242] oil-line electrostatic sensors. The concept has been tested for WECs in WT gearboxes as well [243].…”
Section: Electromagnetic Testing (Et)mentioning
confidence: 99%
“…It has been discussed in the literature that manifestation of electrical discharges, due to the presence of a shaft voltage and the dielectric properties of the lubricant, drives fluting and corrugation damages [ 18 ]. However, recent studies have revealed that at much lower current densities, e.g., <1 mA/mm 2 , bearings’ life has been significantly reduced (to 5–10% of the expected L 10 life) due to the formation of WECs, but often combined with the presence of critical lubricants [ 19 , 20 , 21 ]. In these studies, it was concluded that the electrical discharges promote the formation of WECs [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that at much lower current densities, e.g., <1 mA/mm 2 , bearings’ life has been significantly reduced (to 5–10% of the expected L 10 life) due to the formation of WECs, but often combined with the presence of critical lubricants [ 19 , 20 , 21 ]. In these studies, it was concluded that the electrical discharges promote the formation of WECs [ 19 , 20 , 21 ]. As illustrated in Figure 1 , the electrical circuit of a bearing race-lubricant-rolling element (a bearing contact) can be simplified as a capacitor in parallel with a resistor [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic emission (AE) refers to an acoustic signal that is generated when the strain energy that is formed locally in a solid material is rapidly released [ 4 ]. AE is used for detecting predicted fractures in bearings [ 5 ], gearboxes [ 6 ], pressure vessels [ 7 ], and pipes [ 8 , 9 ] at many sites in the industry. Moreover, an AE signal is generated when an object is plastically deformed or fractured.…”
Section: Introductionmentioning
confidence: 99%